THE NEUTRAL AREA SURFACE OF THE CUBIC MESOPHASE - LOCATION AND PROPERTIES - CHUNG, H; CAFFREY, M (BIOPHYSICAL SOCIETY, 1994)
A neutral area surface can be defined as one whose area remains fixed upon bending. It is assumed that such a surface exists within the amphiphilic monolayers that constitute the bicontinuous cubic mesophases and that it parallels approximately the highly convoluted polar/apolar interlace in such systems. Here, we report on how the neutral area surface in the cubic phase (space group la3d) of the hydrated monoacylglycerol, monoolein, was determined. It is located at a distance of similar to 8.8 Angstrom from the methyl terminus of the acyl chain. At 25 degrees C, the surface area per lipid molecule at the neutral area surface is 35.1 +/- 0.2 Angstrom(2), which is remarkably similar to the mean cross-sectional area of hydrated monoolein in the lamellar liquid crystalline phase at this same temperature.
Keywords: STRONGLY CURVED MONOLAYERS; ELASTIC-MODULI; TRANSITIONS; CURVATURE; CRYSTALS; PHASES